1998
DOI: 10.1001/archotol.124.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Rapid Intraoperative Parathyroid Hormone Assay in the Surgical Management of Parathyroid Disease

Abstract: The intraoperative rapid PTH assay may be of significant benefit in permitting directed unilateral parathyroid explorations for adenoma when combined with preoperative localization with a technetium-99m sestamibi scan. Additionally, the rapid PTH assay has proved to be of benefit in confirming excision of all hyperfunctioning parathyroid tissue in patients with multiple gland hyperplasia, particularly those who may harbor ectopic parathyroid tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Use of preexcision samples has been suggested to reduce the number of false-negative results in patients with a single adenoma (33,42 ). Timing of postexcision samples is generally at 5 and/or 10 min, although timings of 7 and 20 min have been used in reported studies (44,45 ). A recent protocol has suggested that an immediate post-gland excision sample may also be useful (46 ).…”
Section: Interpretation Of Rapid Intraoperative Pth Assay Resultsmentioning
confidence: 99%
“…Use of preexcision samples has been suggested to reduce the number of false-negative results in patients with a single adenoma (33,42 ). Timing of postexcision samples is generally at 5 and/or 10 min, although timings of 7 and 20 min have been used in reported studies (44,45 ). A recent protocol has suggested that an immediate post-gland excision sample may also be useful (46 ).…”
Section: Interpretation Of Rapid Intraoperative Pth Assay Resultsmentioning
confidence: 99%
“…was superior to that of achieving an absolutely normal limit with postexcision levels. Application of the 50% degradation rule to variable time intervals, especially in regard to baseline values (preincision vs. preexcision), has been shown to produce differences in surgical results [67][68][69][70] . Chiu et al [71] applied their institutional IOPTH results to variable interpretation criteria, concluding that utilization of a preincision baseline value and a 10-min postexcision level represented the criteria with the highest predictive value for achieving normocalcemia postoperatively.…”
Section: Methodology and Applicationmentioning
confidence: 99%
“…The rapid intra-operative parathyroid hormone assay (RI-PTH) is transforming the parathyroidectomy procedure. The visualization of all parathyroids glands and resection of apparently enlarged gland(s) has increasingly been replaced by minimally invasive (unilateral) surgical procedures (MIP), supported by pre-operative imaging aid and RI-PTH measurements [2][3][4][5][6][7][8][9][10]. In most cases, the improved imaging techniques enable exact pre-operative localization of the parathyroid adenoma [11].…”
Section: Introductionmentioning
confidence: 99%